1993
DOI: 10.1002/macp.1993.021940627
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady diffusion kinetics of Ziegler‐Natta heterogeneous catalyst polymerization, 4. Prediction of experimental results of propylene/ethylene/1‐hexadecene terpolymerization

Abstract: The prediction, based on unsteady diffusion kinetics, of the enhancement of reactivity and incorporation of 1-hexadecene in its copolymerization with propylene on adding a small amount of ethylene (increase from 5,2 mol-Vo to 10,8 mol-Yo when 2% of ethylene was added, and to 16,l mol-Yo when 5% was added) was verified in the terpolymerization of propylene/l-hexadecene/ ethylene on a commercial Solvay-type 6-TiC1, catalyst. The catalyst efficiency was thus also increased. These augmentations originate from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Other researchers have demonstrated that unsteady diffusion kinetics can predict that the reactivity of 1‐hexadecene with propylene in a heterogeneous Ziegler–Natta copolymerization should increase by two to three times by adding a small amount of ethylene 11. Those researchers had found that terpolymers with 2–10 mol % of 1‐hexadecene as well as small amounts of ethylene incorporated (2–10 mol %) show both lower mps and crystallinity than corresponding copolymers (up to 5–10 °C in T m and five to eight times in crystallinity values).…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have demonstrated that unsteady diffusion kinetics can predict that the reactivity of 1‐hexadecene with propylene in a heterogeneous Ziegler–Natta copolymerization should increase by two to three times by adding a small amount of ethylene 11. Those researchers had found that terpolymers with 2–10 mol % of 1‐hexadecene as well as small amounts of ethylene incorporated (2–10 mol %) show both lower mps and crystallinity than corresponding copolymers (up to 5–10 °C in T m and five to eight times in crystallinity values).…”
Section: Introductionmentioning
confidence: 99%
“…For these researchers, in the terpolymerization of ethylene/propylene/1‐hexadecene the diffusion coefficient of monomer is in the following order: ethylene > propylene > 1‐hexadecene. Then, the extent of the increase in monomer concentration, if it is not in equilibrium, will be 1‐hexadecene > propylene > ethylene 28…”
Section: Resultsmentioning
confidence: 99%
“…The relation between these can be determined analytically using techniques such as temperature rising elution fractionation (TREF)7 and the more recent crystallization analysis fractionation (CRYSTAF) 8–10. The great variability observed in such work is attributed to great variation in different catalyst sites associated with Z–N materials,11, 12 which has been attributed to variations in the diffusion of the different monomers to active sites 13, 14. Such variation can be deliberately introduced15 and is particularly apparent in VLDPEs, which are in effect a reactor blend of different materials ranging from high‐density PE to uncrystallizable rubber‐like material, and where comparing fractionation by direct extraction (according to molar mass) and by crystallization/dissolution (similar to TREF) shows a strong correlation between branch content and molar mass 6.…”
Section: Introductionmentioning
confidence: 99%